2023
DOI: 10.3389/fpls.2022.1074395
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress tolerance mechanisms and their potential common indicators to salinity, insights from the wild watermelon (Citrullus lanatus): A review

Abstract: Climate change has escalated the effect of drought on crop production as it has negatively altered the environmental condition. Wild watermelon grows abundantly in the Kgalagadi desert even though the environment is characterized by minimal rainfall, high temperatures and intense sunshine during growing season. This area is also characterized by sandy soils with low water holding capacity, thus bringing about drought stress. Drought stress affects crop productivity through its effects on development and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 260 publications
(294 reference statements)
0
4
0
Order By: Relevance
“…Drought stress resulted in reduced stomatal aperture in all watermelon genotypes in this study (Figures 5 and 6), and a highly significant reduction was recorded under extreme drought stress (days 6 and 9). The lowest value for stomatal aperture (14.7) was recorded in Clm-03 on day 9 of drought stress, and this is in line with the drought stress avoidance mechanism reported in [54,55]. Another study [54] reported that both medium and severe droughts led to significant decreases in stomatal aperture in drought-stressed maize (Zea mays) plants compared with well-watered plants.…”
Section: Discussionsupporting
confidence: 79%
“…Drought stress resulted in reduced stomatal aperture in all watermelon genotypes in this study (Figures 5 and 6), and a highly significant reduction was recorded under extreme drought stress (days 6 and 9). The lowest value for stomatal aperture (14.7) was recorded in Clm-03 on day 9 of drought stress, and this is in line with the drought stress avoidance mechanism reported in [54,55]. Another study [54] reported that both medium and severe droughts led to significant decreases in stomatal aperture in drought-stressed maize (Zea mays) plants compared with well-watered plants.…”
Section: Discussionsupporting
confidence: 79%
“…A close association between Ran and plant responses to environmental stresses, such as salinity [ 39 ], osmotic stress [ 8 ], drought [ 7 ], low temperatures [ 9 , 40 ], aluminum toxicity [ 41 ], and oxidative stress [ 11 ], has been elucidated in numerous studies. However, the understanding of the underlying mechanisms is slowly improving, and there have been rare reports about the role of longan Ran in defense responses.…”
Section: Discussionmentioning
confidence: 99%
“…Ras-related nuclear protein (Ran) GTPases, also known as molecular switches, play a universal role in nucleocytoplasmic transport, specifically expressed during embryogenesis, and are essential for cell division in animal development [ 4 , 5 ]. Plant Ran GTPases, along with their cofactors and nucleoporins, are involved in diverse biological processes including plant growth and root development [ 6 , 7 ], regulation of hormone (such as auxin and abscisic acid, ABA) sensitivity [ 6 , 8 , 9 ], enhancement of disease resistance [ 10 ], and stress responses, such as those to drought, salinity, osmotic stress, and cold and oxidative stresses [ 7 , 8 , 11 ]. This indicates that plant Ran may have a remarkable impact on plant growth and, hence, its economic traits when overexpressed.…”
Section: Introductionmentioning
confidence: 99%
“…With global warming and increasing water scarcity, drought stress can severely affect the yield and quality of watermelon plants and has become one of the main problems in watermelon cultivation (Malambane et al, 2023). With the development of sequencing technology and molecular biology, analyzing the molecular mechanisms of watermelon drought resistance and identifying functional genes are important for overcoming this problem (Song et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Watermelon plants produce low-calorie and high-fiber fruits that help control weight, promote digestive health, and contain natural antioxidants (Naz et al, 2014). With global warming and increasing shortages of water resources, drought has become one of the main abiotic stresses that impacts the normal growth of plants and substantially reduces the yield and quality of watermelon plants; thus, drought is one of the main problems faced during watermelon cultivation (Malambane et al, 2023). Therefore, studying the mechanism underlying watermelon drought resistance and identifying key drought resistance genes are highly important for ensuring the sustainable development of the watermelon industry (Malambane et al, 2023).…”
Section: Introductionmentioning
confidence: 99%